The Economics of Water Rules and Institutions - Meran, Georg (Springer Water, 2021)
This open access textbook provides a concise introduction to economic approaches and mathematical methods for the study of water allocation and distribution problems. Written in an accessible and straightforward style, it discusses and analyzes central issues in integrated water resource management, water tariffs, water markets, and transboundary water management. By illustrating the interplay between the hydrological cycle and the rules and institutions that govern today's water allocation policies, the authors develop a modern perspective on water management. Moreover, the book presents an in-depth assessment of the political and ethical dimensions of water management and its institutional embeddedness, by discussing distribution issues and issues of the enforceability of human rights in managing water resources. Given its scope, the book will appeal to advanced undergraduate and graduate students of economics and engineering, as well as practitioners in the water sector, seeking a deeper understanding of economic approaches to the study of water management.